Zeolite NPO‐Type Azolate Frameworks. (14th July 2022) - Zha, Xiangyi; Li, Xinhao; Al‐Omari, Abdulhadi A.; Liu, Shan; Liang, Cong‐Cong; Al‐Ghourani, Ala'a; Abdellatief, Mahmoud; Yang, Jingjing; Nguyen, Ha L.; Al‐Maythalony, Bassem; Shi, Zhaolin; Cordova, Kyle E.; et al.
Abstract: Three‐membered rings (3‐rings) are an important structural motif in zeolite chemistry, but their formation remains serendipitous in reticular chemistry when designing zeolitic imidazolate frameworks (ZIFs). Herein, we report a design principle for constructing four new ZIFs, termed ZIF‐1001 to ‐1004, from tetrahedral Zn II centers (T), benzotriazolate (bTZ), and different functionalized benzimidazolates (RbIM) that adopt a new zeolite NPO‐type topology built from 3‐rings. Two factors were critical for this discovery: i) incorporating the bTZ linker within the structures formed 3‐rings due to a ∠(T−bTZ−T) angle of 120–130° reminiscent of the ∠(Ge−O−Ge) angle (130°) observed in germanate zeolite‐type structures having 3‐rings; and ii) RbIM guided the coordination chemistry of bTZ to bind preferentially in an imidazolate‐type mode. This series' ability to selectively capture CO2 from high‐humidity flue gas and trap ethane from tail gas during shale gas extraction was demonstrated. Abstract : A new design principle for obtaining zeolitic imidazolate frameworks (ZIFs) with an underlying NPO built from three‐membered rings (3‐rings) is reported. Among the hundreds of unique ZIFs known, only a few have been discovered that are partially constructed from 3‐ring motifs. These findings provide a significant addition to the limited library of ZIF design principles to access attractive structural features for realizing practical function.